2007
DOI: 10.1007/s00247-007-0491-4
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of CT and MRI in retinoblastoma for the diagnosis of postlaminar invasion with normal-size optic nerve: a retrospective study of 150 patients with histological comparison

Abstract: Our results suggest that MRI is more relevant than CT for preoperative detection of optic nerve invasion in patients with retinoblastoma. Tumour diameter is the only indirect sign significantly associated with postlaminar invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
79
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 24 publications
2
79
1
1
Order By: Relevance
“…Non-EP DWI was performed by using a HASTE sequence with b-values of 0 and 1000 s/mm 2 . ADC values were measured for enhancing and nonenhancing tumor tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Non-EP DWI was performed by using a HASTE sequence with b-values of 0 and 1000 s/mm 2 . ADC values were measured for enhancing and nonenhancing tumor tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Galluzzi et al 18 published a series of 16 eyes and found a correlation between histopathologic optic nerve and/or choroid invasion and AES enhancement on MR imaging; however, no correlation between clinical or histopathologic presence of IA and AES enhancement could be detected. On the other hand, Brisse et al 8 could not confirm this correlation between AES enhancement and optic nerve invasion in 10 eyes. To our knowledge, the present investigation is the most comprehensive study so far in the search for an explanation for variable AES enhancement in retinoblastoma, which confirmed the role of IA in vivo.…”
Section: Discussionmentioning
confidence: 86%
“…6,8,18 Authors of these studies correlated AES enhancement with clinical and histopathologic findings. De Graaf et al 6 reported the clinical presence of IA, hyperemia, or inflammation as possible explanations for AES enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations